Association Between Perceived Threat and the Development of Posttraumatic Stress Disorder Symptoms in Patients With Life‐threatening Medical Emergencies. (24th November 2019) - Moss, Jeena; Roberts, Michael B.; Shea, Lisa; Jones, Christopher W.; Kilgannon, Hope; Edmondson, Donald E.; Trzeciak, Stephen; Roberts, Brian W.
Abstract: Background: Our objectives were to test whether during a potentially life‐threatening medical emergency, perceived threat (a patient's sense of life endangerment) in the emergency department (ED) is common and associated with the subsequent development of posttraumatic stress disorder (PTSD) symptoms. Methods: This study was an ED‐based prospective cohort study in an academic hospital. We included adult patients requiring acute intervention in the ED for resuscitation of a potentially life‐threatening medical emergency, defined as respiratory or cardiovascular instability. We measured patient‐perceived threat in the ED using a validated patient self‐assessment measure (score range = 0 to 21, with higher scores indicating greater perceived threat). We performed blinded assessment of PTSD symptoms 30 days after discharge using the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders‐Fifth Edition (PCL‐5). Results: Ninety‐nine of 113 (88%) patients completed follow‐up, with 98% reporting some degree of perceived threat, median (interquartile range [IQR]) perceived threat score 12 (6 to 17), and 72% reported PTSD symptoms in relation to their ED visit (median [IQR] PCL‐5 score = 7 [0 to 30]). Patients with respiratory instability had higher median (IQR) perceived threat scores (16 [9 to 18] vs. 9 [6 to 14)] and PCL‐5 scores (10 [2 to 40] vs. 3 [0 to 17]) compared to patients without respiratory instability. In a multivariable linear regression model adjusting for potential confounders, greater perceived threat in the ED was independently associated with higher PCL‐5 scores (β = 0.79, 95% confidence interval [CI] = 0.15 to 1.42). Among the individual perceived threat items, the feeling of helplessness during resuscitation had the strongest association with PCL‐5 score (β = 5.24, 95% CI = 2.29 to 8.18). Conclusions: Perceived threat during potentially life‐threatening emergencies is common and independently associated with development of PTSD symptoms. Additional research to test whether reduction of perceived threat in the ED attenuates the development of PTSD symptoms following potentially life‐threatening emergencies is warranted.